Hegemons, leaders and followers: A game-theoretic approach to the postwar dynamics of international political economy - Kjell Hausken; Thomas Plümper (Max-Planck-Institut für Gesellschaftsforschung, 1996)
The article introduces the concept of hegemony to leadership theory, which has developed mainly as a critique of hegemonic stability theory. We argue that it makes sense to combine the two theories by introducing the concept of 'size' into neoliberal thinking about International Political Economy. We accept the neo-institutional hypothesis that a hegemon is not needed to provide public goods, and demonstrate with non-cooperative games how multiple leaders may jointly provide public goods. A game-theoretic model is developed illustrating with Nash equilibria the conditions under which a hegemon rationally switches from hegemony to leadership. It also shows why followers rationally switch from free-riding in their consumption of the public goods to taking part in leading, in the sense of contributing to covering the cost of the production of the public goods. The emergence of joint leadership leads to multiple equilibria in the sense of allowing for multiple stable leadership constellations. The actors are in a mixed-motive or coordination game where they have different preferences for the equilibria, and thus different preferences for which strategies to choose, and for who is to take part in covering the cost of the production of the public goods. Two aspects of joint leadership 'after hegemony' are treated, namely coercive and benevolent leadership on the one hand, and collective action in the sense of joint leadership on the other hand. Finally, future leadership constellations and the quest for international order are discussed. – – Der Artikel führt das Konzept der Hegemonie in die Leadership-Theorie ein, die ursprünglich als Kritik an der Theorie hegemonialer Stabilität entstand. Es macht jedoch Sinn, die zwei Theorien auf der Grundlage einer Konzeption der Akteursgröße innerhalb der neoliberalen Internationalen Politischen Ökonomie zu kombinieren. Ausgehend von der These des Neo-Institutionalismus, daß die Existenz eines Hegemons keine notwendige Bedingung für die Produktion öffentlicher Güter ist, wird mit Hilfe der nicht-kooperativen Spieltheorie gezeigt, wie verschiedene 'leaders' gemeinsam öffentliche Güter produzieren können. Darauf aufbauend wird ein spieltheoretisches Modell entwickelt, welches Nash-Gleichgewichte benutzt, um die Bedingungen zu illustrieren, unter denen es für ein Hegemon rational ist, für gemeinsame 'leadership' zu optieren. Gleichzeitig wird verdeutlicht, warum 'followers' rational ihr Trittbrettfahren einstellen und sich an der Bereitstellung der öffentlichen Güter beteiligen. Dies führt zur Ausprägung von multiplen Gleichgewichten. Die Akteure finden sich in einem Koordinationsspiel, in dem sie jeweils unterschiedliche Gleichgewichte und damit auch unterschiedliche individuelle Strategien präferieren. Der Konflikt entsteht an der Frage, welche Akteure sich 'after hegemony' an der Produktion der öffentlichen Güter beteiligen. Dabei sollte zwischen wohlwollend und zwangsgestützten 'Joint-leadership'-Systemen einerseits und impliziten gemeinsamen Aktionen andererseits unterschieden werden. Abschließend werden mögliche, vom Modell nahegelegte, künftige Leadership-Konstellationen und die sich daraus ergebende internationale Ordnung diskutiert.
Keywords: 300